Fortalecimiento del canal comercial corporativo en servicios internacionales para Avianca Deprisa, en el Departamento Quindío (2017)
Make This Work potentiate paragraph Hurry International Product in the Quindío For Postal Services Company Specialized AUTHORIZED BY Avianca-Quickly Developing strategies for increasing sales of this product, the customer acquisition, maintenance, and support potentiation Current of doing great business management focused on international corporate channel area a national level is one of the most profitable para The Management Company exports and imports Courier para All our country from the world, having a favor of our great potential and strength that has this Product in other regions of our country being listed as one of the products that paragraph genres Avianca income quickly. International Economic Relations and customers need fast by Avianca incorporated into the challenges of economic growth son A competitive reality, reason esta quickly created by Avianca Transportation Strategies Worldwide in order that their clients can be expanded and reach more than 260 countries, rely on para This Strategies and Alliances implemented logistics international air transport A leading company in UPS Worldwide Logistics As it is